Energy intermittency - Sorensen, Bent (CRC Press/Taylor & Francis Group, 2015)
This book addresses energy supply intermittency systematically. Offering a scholarly assessment and collection of the existing literature, the text describes different levels of variability for traditional and renewable energy sources, presenting detailed solutions for handling energy intermittency through trade, collaboration, demand management, and active energy storage. It also provides simulation studies regarding resource time-flow, energy conversion devices, and demand structure to assist energy planners and system-responsible entities in government agencies and private energy enterprises in evaluating the technical viability of the proposed solutions